Identification of Potential and Suitability of Bagek Kembar Mangrove Forest, Cendi Manik, Sekotong, Lombok Barat as a Tourist Attraction - Amini, Elda Risa; Hadiprayitno, Gito; Suana, I Wayan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Mangrove forests have various roles in the environment, and have the potential to be developed as ecotourism areas. The aim of this study is to identify the potential and suitability of the Bagek Kembar mangrove forest as a tourist attraction. Data collection was carried out at two stations, namely natural and rehabilitated mangroves. Samples were taken in plots measuring 10 x 10 meters for mangroves and mobile fauna, and 1 x 1 meter plots for sessile fauna. The Tourism Suitability Index is analyzed based on the number of species, density and thickness of mangroves, number of fauna species, and water depth at high and low tides. The research results show that the Bagek Kembar mangrove forest area is classified as suitable to very suitable for development as an ecotourism area. Tourist attractions that potential to be developed are educational, birdwatching and culinary.